Reprod Med Int 2018
DOI: 10.23937/rmi-2017/1710006
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Paradigms for Measuring Peak Serum Relaxin in Eumenorrheic, Active Females

Abstract: Relaxin is a member of the insulin-like superfamily and is primarily recognized for facilitating vaginal delivery by increasing pelvic ligament laxity [8]. There are three known relaxin peptides in humans, each with varying functions [8]. Whereas relaxin-1 and relaxin-2 regulate collagen expression, metabolism in fibroblasts, and changes in proteolytic enzymes in the corpus luteum, decidua, and endometrium, relaxin-3 is specific to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The participants in our study reported relaxin ranging from 0-59 pg/ mL with 15 athletes being above the 6.0 pg/mL threshold. Previous studies have reported peak SRC to be 49.6 ± 30.5 pg/mL [25], suggesting most of the values collected in this study are not at peak SRC; however, SRCs for athletes 22-24 days after the start of the menstrual cycle were reported as 6.0 ± 8.1 pg/mL for athletes who tore their ACL and 1.8 ± 3.4 pg/mL for athletes who did not tear their ACL [11]. The athletes from our study reported SRC of 11.3 ± 12.6 pg/mL, suggesting participants were in range for the measurement period.…”
Section: Discussionmentioning
confidence: 86%
“…The participants in our study reported relaxin ranging from 0-59 pg/ mL with 15 athletes being above the 6.0 pg/mL threshold. Previous studies have reported peak SRC to be 49.6 ± 30.5 pg/mL [25], suggesting most of the values collected in this study are not at peak SRC; however, SRCs for athletes 22-24 days after the start of the menstrual cycle were reported as 6.0 ± 8.1 pg/mL for athletes who tore their ACL and 1.8 ± 3.4 pg/mL for athletes who did not tear their ACL [11]. The athletes from our study reported SRC of 11.3 ± 12.6 pg/mL, suggesting participants were in range for the measurement period.…”
Section: Discussionmentioning
confidence: 86%